The Runaway Racehorse - Roy, Ron 1940-; Gurney, John (New York : Random House, 2002)
Dink, Josh, and Ruth Rose investigate the disappearance of a valuable racehorse that Dink's uncle and his friend, Forest Evans, have just bought and entered in a race at Saratoga.
Keywords: Race horses -- Fiction; Horses -- Fiction; Mystery and detective stories; Larchmont (N.Y.) -- Fiction